Effects Of Fractionation Technique On Triacylglycerols, Melting And Crystallisation And The Polymorphic Behavior Of Bambangan Kernel Fat As Cocoa Butter Improver - Norazlina M.R.; Jahurul M.H.A.; Hasmadi M.; Patricia M.; Lee J.S.; Amir H.M.S.; Noorakmar A.W.; Riman I.; Sharifudin Md Shaarani (Elsevier, 2024)
LWT Volume 129, July 2020